RIBA (USURY OR TAKING AND CHARGING INTEREST) - Hadi, Sholikhul (ZISWAF, 2014)
Riba is an exchange of Ribawi elements where there is a difference in timeand/or quantity. The Ribaaawi elements mentioned by the prophet are gold forgold, silver for silver, wheat for wheat, barley for barley, dates for dates, andsalt for salt. By a similar analogy, money is similar to gold and silver whereit is a modern way of exchange. Therefore a contract of exchange between theinsurer and insured contains a Ribawi element, i.e. levels of compensationinvolving varying amounts and time scales.The strict prohibition of interest in Islam is because of the following reasons.(Qaradawi, 2001). Taking of interest implies appropriating aanother person’sproperty without giving them aanything in exchange, because the one whomlends the other one dollar for one dollar plus gets the extra for nothing.Dependent on interest prevent people from working to earn money, sincethe person with one dollar can earn extra dollars through interest either inadvance or on later date without working for it. If it is happen to capital ownerthen they would not invest in the industry, trade and commerce, building andconstruction, as they will get extra earning without necessarily doing all ofthe hard work.Permitting the taking of interest discourages people from doing good toone another. If interest is prohibited in a society, people will lend to each otherwith a good will, expecting back no more then what they have lent. Riba isalso totally prohibited in Islam as because it tends to create unfair or injusticetreatment between one party with another. It also exploits one by the others.In Ribawi economic the rich one tends to get more benefit compares with thepoor one. The gap between the rich one and the poor one is becoming bigger andbigger as Riba have a spiral impact on increasing price for goods.